KINERJA LAYANAN BIS KOTA DI KOTA SURABAYA - Supriyatno, Dadang; Widayanti, Ari (Jurnal Transportasi, 2010)
The bus service in Surabaya is far from adequate and there is a need to evaluate the bus performance from time to time. The purpose of this study is to measure the bus performance on 21 service routes in Surabaya. The performance indicators used consist of frequency, headway, load factor, and travel time. The results show that only load factor and travel time are indicating that the bus service is good, while frequency and headway indicators suggest that the bus service needs to be enhanced.Keywords: service performance, frequency, load factor, headway, travel time